2005
DOI: 10.1097/00008469-200502000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer screening: another point of view

Abstract: The breast cancer screening programmes (BCSP) are very controversial at the present time. They are evaluated by different socio-economic sectors, each with its own particular point of view. Large numbers of breast cancer cases are concentrated in the Oncology Services, which are, therefore, sensitive to the changes that these programmes could bring about. All patients attending the medical oncology and radiotherapy services of the Reina Sofia University Hospital, Cordoba from January 1994 until January 2003 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…The results of this study showed that patients with screeningdetected tumours had less advanced breast carcinoma: AJCC stage 0/1, in-situ tumour and SBR grade 1. These results are in agreement with earlier findings (Taba'r et al, 1985;Burrell et al, 1996;Porter et al, 1999;Ernst et al, 2004;O'Regan, 2004;De la Haba Rodríguez et al, 2005;Dawson et al, 2009). Screening-detected tumours are more likely to be of low grade or in situ because mammography allows the detection of breast cancer in its preclinically detectable phase.…”
Section: Discussionsupporting
confidence: 93%
“…The results of this study showed that patients with screeningdetected tumours had less advanced breast carcinoma: AJCC stage 0/1, in-situ tumour and SBR grade 1. These results are in agreement with earlier findings (Taba'r et al, 1985;Burrell et al, 1996;Porter et al, 1999;Ernst et al, 2004;O'Regan, 2004;De la Haba Rodríguez et al, 2005;Dawson et al, 2009). Screening-detected tumours are more likely to be of low grade or in situ because mammography allows the detection of breast cancer in its preclinically detectable phase.…”
Section: Discussionsupporting
confidence: 93%